The Youth Guarantee System in Spain: tailored youth policy or broad-brush employment policy? - Joan Rodríguez-Soler; Joan Miquel Verd (Social Work and Society, 2019)
This article presents an analysis of the general approach and the specific measures of the Youth Guarantee Programme in Spain, using the analytical tools of the Capability Approach. The objective is to study to what extent the design of the actions of the youth guarantee can be effective taking into account the characteristics of the group to which they are addressed: young people with difficulties to enter the labour market. The analysis leads us to conclude that there are reasonable doubts in relation to the level of adjustment between the general design and the specific measures of the Spanish Youth Guarantee Programme and the characteristics of its target population. Thus, the several obstacles to ensuring that the resources devoted to youth guarantee have the desired effects become evident.